Radiotherapy combined with TLR7/8 activation induces strong immune responses against gastrointestinal tumors - Schölch, Sebastian; Rauber, Conrad; Tietz-Dalfuß, Alexandra; Schmidt, Thomas; Haberkorn, Uwe; Huber, Peter E. (OncoTarget, 2014)
In addition to local cytotoxic activity, radiotherapy may also elicit local and systemic antitumor immunity, which may be augmented by immunotherapeutic agents including Toll-like receptor (TLR) 7/8 agonists. Here, we investigated the ability of 3M-011 (854A), a TLR7/8 agonist, to boost the antigen-presenting activity of dendritic cells (DC) as an adjuvant to radiotherapy. The combined treatment induced marked local and systemic responses in subcutaneous and orthotopic mouse models of colorectal and pancreatic cancer. In vitro cytotoxicity assays as well as in vivo depletion experiments with monoclonal antibodies identified NK and CD8 T cells as the cell populations mediating the cytotoxic effects of the treatment, while in vivo depletion of CD11c+ dendritic cells (DC) in CD11c-DTR transgenic mice revealed DC as the pivotal immune hub in this setting. The specificity of the immune reaction was confirmed by ELISPOT assays. TLR7/8 agonists therefore seem to be potent adjuvants to radiotherapy, inducing strong local and profound systemic immune responses to tumor antigens released by conventional therapy.